Bottom sealing and photoelectrochemical properties of different types of anodic TiO2 nanotubes - Lee, Kiyoung; Schmuki, Patrik (Electrochimica Acta, 2013)
Over the past years, the photoelectrochemical behavior of anodic TiO2 nanotubes has intensively been investigated. However, comparably little attention has been paid to the large influence of growth parameters on the phtoelectrochemical tube properties. In the present work we investigate nanotubes of comparable geometry but using either aqueous electrolytes or different organic electrolytes. We show that very drastic differences in their photoresponse can be obtained. Moreover, we show that a recently introduced tube bottom sealing treatment has a very different effect on different tube types and strongly affects the performance of nanotube layers in dye sensitized solar cells.
EAM Import::2019-03-13